Uso de gêneros textuais multimodais no ensino de língua inglesa em escola pública - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The English language has an important status in our current globalized world. The development of new communication technologies greatly contributed to this. Through the improvement of these technologies, new textual genres with multimodal characteristics and new forms of literacy have emerged. Considering this tendency, a group of researchers known as The New London Group warned, yet at 1996, about the necessity to incorporate these new forms of communication to classroom practices. The goal of this work was to investigate the pedagogical potential and the acceptance of these new multimodal genres by students in the English language classes at a public school, through a didactic sequence of 15 hours. As a result, it was possible to notice a change at the concept students had about English language teaching and learning at public schools, and their gradual engagement during the activities proposed in class at the moment they had contact to these genres they already have familiarity through their daily activities out of classroom.
Keywords: Letras; Língua inglesa; Multiletramentos; Multimodalidade; Ensino; Escola pública; CNPQ::LINGUISTICA, LETRAS E ARTES